USM HEALTH CAMPUS WELCOMES SEYCHELLES DELEGATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 2 December, 2016 – The Health Campus of Universiti Sains Malaysia (USM) continues to welcome international visitors, with an official courtesy call from the delegates of Seychelles Islands being the latest.